Characterization and Bioactive Compound Analysis of Meretrix meretrix Linnaeus - Apriandi, Azwin; Tarman, Kustiariyah; Sugita, Purwantiningsih (Marinade, 2018)
Meretrix meretrix was one of gastropods seawater has been used by people as a food. These shells are still categorized of bycatch and have not explored the benefits. This study aimed to characterize and analyze the content of bioactive Meretrix meretrix. This research was conducted morphological characterization shellfish sensory, measurement of yield, the content of the proximate analysis, heavy metals and analysis of bioactive compounds from the extracts of water and methanol. Observation found that the Meretrix meretrix has a yellowish white color with black bars at the end of the shell and the white meat and chewy with a yield of meat and shells of 11.09% and 69.85%. Analysis of water content, ash, fat, protein, and carbohydrates respectively by 79.99%, 1.50%, 0.22%, 9.42%, and 8.81%. Heavy metal obtained  8x10-4 ppm Hg content, 13x10-4 ppm Pb, Cd, and Cu 45x10-4 and 88x10-4 ppm. Bioactive compounds in water and methanol extract of shellfish Lamis including alkaloids, steroids, and saponins.